2014
DOI: 10.1063/1.4901401
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural analysis of 9.7% efficient Cu2ZnSnSe4 thin film solar cells

Abstract: This work presents a detailed analysis of the microstructure and the composition of our record Cu 2 ZnSnSe 4 (CZTSe)-CdS-ZnO solar cell with a total area efficiency of 9.7%. The average composition of the CZTSe crystallites is Cu 1.94 Zn 1.12 Sn 0.95 Se 3.99. Large crystals of ZnSe secondary phase (up to 400 nm diameter) are observed at the voids between the absorber and the back contact, while smaller ZnSe domains are segregated at the grain boundaries and close to the surface of the CZTSe grains. An underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…It can be seen that after only 2 min of treatment, the Cu content drops from 10 at.% to less than 1 at.%. Similar evolution was observed for the Zn content which was found to decrease from about 25 at.% (the relatively high initial Zn content being due to the presence of ZnSe secondary phase at the surface of the samples) 23 to 10 at.%. 23 In the meantime, the Sn content drastically increases (from 9 at.% to 22 at.%) accompanied by a shift to higher binding energies of the Sn XPS peak indicating the formation of a Sn-based secondary phase.…”
Section: Cztse Layers Treated In Liquid Phase Ammonium Sulfidesupporting
confidence: 77%
“…It can be seen that after only 2 min of treatment, the Cu content drops from 10 at.% to less than 1 at.%. Similar evolution was observed for the Zn content which was found to decrease from about 25 at.% (the relatively high initial Zn content being due to the presence of ZnSe secondary phase at the surface of the samples) 23 to 10 at.%. 23 In the meantime, the Sn content drastically increases (from 9 at.% to 22 at.%) accompanied by a shift to higher binding energies of the Sn XPS peak indicating the formation of a Sn-based secondary phase.…”
Section: Cztse Layers Treated In Liquid Phase Ammonium Sulfidesupporting
confidence: 77%
“…Furthermore, it can be seen in Figure 7 that voids are present in the CZTSe layer and Cu and Zn rich secondary phases, possibly ZnSe and Cu x Se y , are segregated inside them as commonly observed. 6,38 In both non-annealed as well as annealed sample there are evidences for regions with enhanced Sn and O signal near the voids, suggesting the presents of SnOx, however different to recent auger nanoprobe studies of air annealed CZTSSe absorbers no SnOx is found in the grain boundaries. 9 The highest cell efficency achieved with the combination of KMnO 4 +H 2 SO 4 and Na 2 S etching together with a optimal full cell post deposition annealing treatment of 35 minutes at 200ºC is 8.3% as shown in Figure 7 which was below 3% before post deposition annealing.…”
Section: Influence Of Annealing Treatment On Cztse Bulkmentioning
confidence: 72%
“…Buffière et al . suggested that up to a 40‐nm diameter the ZnSe phase is located near the back contact, and smaller ZnSe phases are segregated at the grain boundaries and near the grains . The Cu‐rich spots and ZnSe phases have a tendency to decompose into the CZTSe phase .…”
Section: Resultsmentioning
confidence: 99%